Population surveys as management tools and health care models - Andrade, Flavia Reis de; Narvai, Paulo Capel (Revista de Saúde Pública, 2013)
The article briefly systematizes health care models, emphasizes the role of population surveys as a management tool and analyzes the specific case of the Brazilian Oral Health Survey (SBBrasil 2010) and its contribution to the consolidation process of health care models consistent with the principles of the Sistema Único de Saúde (SUS, Public Health Care System). While in legal terms SUS corresponds to a health care model, in actual practice the public policy planning and health action, the system gives rise to a care model which is not the result of legal texts or theoretical formulations, but rather the praxis of the personnel involved. Bearing in mind that the management of day-to-day health affairs is a privileged space for the production and consolidation of health care models, it is necessary to stimulate and support the development of technical and operational skills which are different from those required for the management of care related to individual demands.